A simplified technique of pancreas transplantation in a porcine model - Fonouni, Hamidreza; Tahmasbi Rad, Morva; Esmaeilzadeh, Majid; Golriz, Mohammad; Majlesara, Ali; Mehrabi, Arianeb (European surgical research, 2015)
Background: The incidence of diabetes has been steadily increasing. The only curative option for diabetes is pancreas transplantation (PTx). Porcine models are valuable because of their anatomical and physiological similarities to human beings. Our aim is to introduce a simplified technique of PTx in a porcine model. Methods: In Landrace pigs (n = 32), after median laparotomy, the pancreas was mobilized, and the portal and splenic veins were divided. The proper hepatic and splenic arteries and the bile duct were also prepared, and the duodenal bulb was prepared and stapled. The third portion of the duodenum was freed up to the ligament of Treitz and stapled, and the renal arteries were ligated. After systemic heparinization, the pancreas was perfused through the abdominal aorta with histidine-tryptophan-ketoglutarate solution. The portal and splenic veins were cut for evaluating the sufficiency of perfusion. Whole pancreaticoduodenal graft was procured along with an aortic jump graft containing mesenteric and celiac trunks. In recipients, after total pancreatectomy, the suprarenal inferior vena cava and infrarenal aorta were prepared for vascular anastomosis in an end-to-side manner. After pancreas reperfusion, duodenoduodenostomy was performed in an end-to-side manner. Results: Median cold and warm ischemia times were 10 h (range, 9-14 h) and 50 min (range, 35-80 min), respectively. The hemodynamic status was stable throughout the operation. The median follow-up period was 7 days (range, 4-10). There were no major intra- and postoperative complications. Conclusion: By using an aortic jump graft, there was no need to perform additional arterial reconstruction resulting in a short warm ischemic and operation time. End-to-side portocaval and duodenoduodenal anastomoses make this model of PTx a very feasible method for experimental evaluations.